CONSTRUCTIVISM AND REFLECTIVISM AS THE LOGICAL COUNTERPARTS IN TESOL: LEARNING THEORY VERSUS TEACHING METHODOLOGY - Abdullah al Mahmud (TEFLIN, 2013)
The gist of the entire constructivist learning theory is that learners are self-builders of their learning that occurs through a mental process in a social context or communication setting, and teachers as facilitators generate learning by creating the expected environment and/or utilizing the process. This article theoretically proves reflectivism as the logical counterpart of constructivism through establishing their complete interdependence andthen suggests certain strategies of reflection to be used in language teaching for ensuring the best possible constructivist learning of language learners. In doing so, Â the basic tenets of constructivism and reflective thoughts are elaborated, examining their mutual connection thoroughly in terms of constructivist recommendations. The research also focuses on three case studies to depict how the theory of constructivist learning principles comes into practice through judicious reviews or reflective process.